Cannabis: Global Histories - Mills, Jim; Richert, Lucas (Cambridge, Massachusetts : The MIT Press, 2021)
"A global history of cannabis that offers a broad, multicontinental examination of the roots and effects of cannabis policy and legalization efforts"
Keywords: Cannabis -- History. -- Social aspects